Analysis Of Profit Planning By Applying The CVP (Cost Volume Profit) Method In The Mommy Yummy Curup Fried Chicken Business - Dwi Sinta; Ardiansyah, Novriza Wahyu (Universitas Dehasen Bengkulu, 2025)
The research uses break-even analysis to determine the target profit that must be achieved. From the calculation at the break-even point, the BEP value for chicken geprek + rice was obtained as 162 units and in rupiah as Rp 1,615,324. This means that to reach a break-even point in sales in rupiah, the product of fried chicken with rice must achieve sales of Rp 1,615,324 or 162 units per month. Based on the calculations above, the BEP value for chicken geprek + rice + rice is obtained in units of 134 units and in rupiah amounting to Rp 2,534,288. This means that to reach a break-even point in sales in rupiah, it must be able to achieve sales of Rp 2,534,288 or 270 units per month. From the calculations above, the BEP value for ayam geprek is obtained as 204 units and Rp1,628,062. This means that to reach a break-even point in sales of Rp1,628,062, 204 units must be sold.